Pemberdayaan Remaja Putra Damarwulan Kepung Melalui Pelatihan Jahit Jilbab - Ahmad Abdul Basyir; Muhammad Faiz Amiruddin (LP3M IAIFA Kediri, 2020)
The progress of Damarwulan village can not be separated from community participation in the empowerment of young men carried out in Damarwulan Kecamatn Village Kepung Kediri Regency. In the progress and high community participation certainly can not be separated from the shortcomings that exist in damarwulan village, therefore researchers as implementers design a program entitled